Serum Anti-Müllerian Hormone Is Significantly Altered by Downregulation With Daily Gonadotropin-Releasing Hormone Agonist: A Prospective Cohort Study - Drakopoulos, Panagiotis; van de Vijver, Arne; Parra, Jose; Anckaert, Ellen; Schiettecatte, Johan; Blockeel, Christophe; Hund, Martin; Verhagen-Kamerbeek, Wilma D. J.; He, Ying; Tournaye, Herman; Polyzos, Nikolaos P. (Frontiers in Endocrinology, 2019)
Research question: What is the effect of gonadotropin-releasing hormone (GnRH)-agonist treatment on serum anti-Müllerian hormone (AMH)? Design: This prospective cohort study conducted in a tertiary university hospital comprised patients (n = 52) who self-administered daily triptorelin (0.1 mg/0.1 mL) subcutaneously for 14 days from menstrual cycle day 21 ± 3, between July 2015 and March 2016. Enrolled women were 18–43 years old, considered normal ovarian responders, with a planned GnRH agonist controlled ovarian stimulation protocol. The primary endpoint was to evaluate the effect of GnRH agonist on serum AMH levels after 7 and 14 days of treatment. Results: Under GnRH agonist treatment, serum AMH was significantly decreased vs. baseline on day 7 (mean change from baseline: –0.265 ng/mL; 95% confidence interval [CI], –0.395 to –0.135 ng/mL; p < 0.001). On day 14, serum AMH was significantly increased (mean change from baseline: 0.289 ng/mL; 95% CI, 0.140–0.439 ng/mL; p < 0.001). Although the median change in AMH from baseline was only –14.9% on day 7 and +17.4% on day 14, from day 7 to 14 AMH significantly increased by 0.55 ng/mL (43.8%; p < 0.001), which is of paramount clinical importance. A linear, mixed-effect model demonstrated that GnRH agonist treatment for 7 and 14 days had a highly significant effect on serum AMH concentration after adjustment for confounding factors (age, body mass index, baseline antral follicle count, and visit). AMH assay precision was excellent (four aliquots/sample); coefficient of variation was 1.2–1.4%. Conclusions: GnRH agonist treatment had a clinically significant effect on serum AMH, dependent on treatment duration. The clear V-shaped response of AMH level to daily GnRH agonist treatment has important clinical implications for assessing ovarian reserve and predicting ovarian response, thus AMH measurements under GnRH agonist downregulation should be interpreted with great caution.